Self-learning at the right level, COVID-19 school closure, and non-cognitive abilities - Minhaj Uddin Mahmud; Yasuyuki Sawada; Mai Seki; Kazuma Takakura (Asian Development Bank Institute (ADBI), 2024)
The COVID-19 pandemic and associated school closures exacerbated the global learning crisis, especially for children in developing countries. Teaching at the right level is gaining greater importance in the policy arena to recover the learning loss. However, the focus on the noncognitive abilities of students influencing their ability to bridge learning gaps is still very limited. We investigate the long-term effects of the "self-learning at the right level" program, which is found to be effective in the short run in improving the cognitive and non-cognitive abilities of disadvantaged students in Bangladesh. We revisit these students almost six years after the intervention to find that its effects on non-cognitive abilities remain perceptible, whereas those on cognitive abilities might have been attenuated. This study is among the few to examine the long-term effects of experimental educational interventions and shows that such interventions can effectively sustain students' non-cognitive abilities amid academic disruptions.
Keywords: I20; O12; 330; self-learning at the right level; COVID-19 school closure; non-cognitive abilities; long-term follow-up